Dysregulation of hexosamine biosynthetic pathway wiring metabolic signaling circuits in cancer - Itano, Naoki; Iwamoto, Shungo (Biochimica et biophysica acta. General subjects, 2023)
Metabolite sensing, a fundamental biological process, plays a key role in metabolic signaling circuit rewiring. Hexosamine biosynthetic pathway (HBP) is a glucose metabolic pathway essential for the synthesis of uridine diphosphate N-acetylglucosamine (UDP-GlcNAc), which senses key nutrients and integrally maintains cellular homeostasis. UDP-GlcNAc dynamically regulates protein N-glycosylation and O-linked-N-acetylglucosamine modification (O-GlcNAcylation). Dysregulated HBP flux leads to abnormal protein glycosylation, and contributes to cancer development and progression by affecting protein function and cellular signaling. Furthermore, O-GlcNAcylation regulates cellular signaling pathways, and its alteration is linked to various cancer characteristics. Additionally, recent findings have suggested a close association between HBP stimulation and cancer stemness; an elevated HBP flux promotes cancer cell conversion to cancer stem cells and enhances chemotherapy resistance via downstream signal activation. In this review, we highlight the prominent roles of HBP in metabolic signaling and summarize the recent advances in HBP and its downstream signaling, relevant to cancer. •Hexosamine biosynthetic pathway serves as a nutrient sensing pathway and wires metabolic signaling circuits.•Dysregulated hexosamine biosynthetic pathway leads to abnormal protein glycosylation and O-GlcNAcylation.•Hexosamine biosynthetic pathway contributes to cancer development and progression.•Elevated hexosamine biosynthetic pathway flux promotes cancer stem cell traits.